Phytosanitary problems in elephant garlic (Allium ampeloprasum var. holmense) in the “Val di Chiana” area (Central Italy), and evaluation of potential control strategies - Francesco TINI; Giovanni BECCARI; Niccolò TERZAROLI; Enrica BERNA; Lorenzo COVARELLI; Mara QUAGLIA (Phytopathologia Mediterranea)
Allium ampeloprasum var. holmense (elephant garlic) is traditionally cultivated in “Val di Chiana”, an area between Umbria and Tuscany regions of Central Italy, under the name “Aglione della Valdichiana”. This product has recently increased in importance, becoming a key economic resource for local farmers. In 2019, phytosanitary problems of elephant garlic cloves ready for transplanting emerged in this cultivation area. Symptom/sign observations and fungal isolations were performed for cloves divided into four components (tunic, basal plate, reserve tissue and shoot) from six farms in the “Val di Chiana” area. Isolates obtained were identified, using partial β-tubulin (BenA) and calmodulin (CaM) or translation elongation factor 1α (tef1α) genes sequences, as belonging to Penicillium [P. allii (95%), P. citrinum (4%), P. brevicompactum (1%)] or Fusarium [F. oxysporum (81%), F. proliferatum (19%)]. Fusarium spp. were mainly associated with clove tunics and basal plates, while Penicillium spp. with basal plates, reserve tissues and shoots. Fungi often also developed from asymptomatic components, but a correlation was found between isolated pathogens and disease symptoms. Pathogenicity and virulence towards elephant garlic cloves were verified for a representative isolate of each identified species, and Penicillium allii was the most virulent. Strategies to control Fusarium and Penicillium spp. on cloves were assessed, including chemicals, a biocontrol agent, surface sterilization and heat treatment. Among these, treatments with Patriot Gold® (active ingredient [a.i.] Trichoderma asperellum TV1, approved in organic farming on crops similar to elephant garlic), or Signum® (a.i. boscalid + pyraclostrobin, approved for Integrated Pest Management systems on crops similar to elephant garlic), were effective in simultaneous reduction of Penicillium spp. and Fusarium spp. Transplanting of asymptomatic cloves combined with the use of the above treatments showed promising effects for pathogens control, and to assist elephant garlic crop establishment.